2007
DOI: 10.1021/es062194+
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Catalytic Hydrogenation of Polyaromatic Hydrocarbon Compounds in Hydrogen−Supercritical Carbon Dioxide

Abstract: A continuous hydrogenation device was evaluated for the detoxification of selected tri-, tetra-, or pentacyclic polyaromatic hydrocarbon (PAH) compounds {anthracene, phenanthrene, chrysene, and benzo[a]pyrene (B[a]P)} by hydrogenation. A substrate stream in hexane, 0.05-1.0% (w/v), was mixed with hydrogen-carbon dioxide (H2-CO2, 5-30% v/v) and delivered to a heated reactor column (25 cm x 1 cm) containing palladium supported on gamma alumina (Pd0/gamma-Al2O3) that was terminated with a capillary restrictor. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…[167] "Real-time" switching to any of the products can be achieved rapidly by simply changing the reactor conditions. While Marshall and co-workers [168] used scCO 2 for the continuous catalytic hydrogenation of polyaromatic compounds, the Recasens group applied supercritical dimethyl ether as reaction solvent for the partial hydrogenation of sunflower oil. [169] Similarly, the Tacke [170] and Härrçd groups [171] reported on the supercritical hydrogenations of fats, relevant to the food industry.…”
mentioning
confidence: 99%
“…[167] "Real-time" switching to any of the products can be achieved rapidly by simply changing the reactor conditions. While Marshall and co-workers [168] used scCO 2 for the continuous catalytic hydrogenation of polyaromatic compounds, the Recasens group applied supercritical dimethyl ether as reaction solvent for the partial hydrogenation of sunflower oil. [169] Similarly, the Tacke [170] and Härrçd groups [171] reported on the supercritical hydrogenations of fats, relevant to the food industry.…”
mentioning
confidence: 99%
“…Triple dosage (90 mg of Mg powder + 180 μL glacial acetic acid) did not show any improvement of PAH degradation (Figures 6 and 7; Table 4). The reduction of PAHs using activated Mg and anhydrous ethanol is selective because only anthracene (9) and fluoranthene (14) in the coal tar were reduced with high removal %. The main products from anthracene and fluoranthene are 9,10-dihydroanthracene and 2,3-dihydrofluoranthene, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic reduction is one of the methods used for PAHs degradation. , For example, transition metals (e.g., rhodium, ruthenium, palladium, etc.) have been successfully used as catalysts in degrading PAHs through hydrogenation, but the procedure requires high temperature and pressure of hydrogen to obtain relatively small nontoxic products.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, partially hydrogenated products, 14H-B[a]P or 12H-Cry, that retained one benzene ring intact, were also without perceptible mutagenic activity in the Ames bacterial reverse mutation assay. 19 The regioselectivity of partial hydrogenations over a carbon-supported Pd vs. Pt catalyst coupled with the deep hydrogenation activities of noble metal catalysts suggested that this initial survey be restricted to a comparison of the hydrogenation activities of supported Pd catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…To address the toxicity of the mobilized PAH contaminants in the washing solution and to recycle the surfactant, 18 a backextraction into hexane was optimized to transfer lipophilic toxicants from the aqueous surfactant soil wash to an organic carrier (hexane) that was subsequently detoxified at line by continuous catalytic de-aromatization (hydrogenation). 19 Hydrogenation over transition metal catalyst(s) to reduce PAHs has been broadly investigated by several researchers. [20][21][22][23][24] Frequently, these hydrogenation reactions have been carried out under elevated temperature and high H 2 pressure.…”
Section: Introductionmentioning
confidence: 99%